INTER-COMMUNAL WAR AND HUMAN SECURITY IN EFFIUM AND EZZA-EFFIUM, EBONYI STATE - NWANGELE, Sunday; OKAFOR, Lawrence Chima; NWEZE, Chinwe Nweze (EBSU Journal of Social Sciences and Humanities, 2024)
This study examines the inter-communal war and human security in Effium and Ezza-Effium, Ebonyi State. Effium and EzzaEffium has been living in peace decades of years past. The peaceful coexistence between Effium and Ezza-Effium was shattered in 2021 due to inter-communal war that destroyed lives, valuables and properties in the community. On methodology, the study used interview and consulted secondary source of information. Group Theory of Conflict was relevant for this study and was used. Effects of Effium and Ezza-Effium inter-communal war were examined under the following sub-headings: Personal security, political security, community security, economic security, food security and health security. Peace and security measures applied by Ebonyi State Government to stop the war were identified. The study discovered the outcome of the inter-communal war between Effium and Ezza-Effium to include increase in urban migration and over-flocking of neighbouring communities, market for sale of arms and ammunitions, loss of life and properties, shortage of food production, living in fear, abuse of fundamental human rights, distrust and so on. The implication of the outcome of the inter-communal war is that peace, security and sustainable development existing in Effium and Ezza-Effium community had been disintegrated. From the findings, it was recommended that major stakeholders should tackle remote causes of conflict once it is identified to avoid such conflict escalating beyond control, Nigeria Security Agents should intensify action toward stoppage of proliferation of arms and ammunition in the country, and group interest should be handled in such a way that it does not bring harm and suffering to all concerned.